2017
DOI: 10.1159/000460251
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Physical Behavior in Late Stage Parkinson Disease Dementia: Differences between Cognitive Subtypes

Abstract: Background: For the early diagnosis of Parkinson disease dementia (PDD), objective home-based tools are needed to quantify even mild stages of dysfunction of the activities of daily living (ADL). Objectives: In this pilot study, home-based physical behavior was assessed to examine whether it is possible to distinguish mild cognitive impairment (PD-MCI) from PDD. Methods: Fifty-five patients with mild to severe Parkinson disease (PD) participated in this cross-sectional study. Based on comprehensive neuropsycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 34 publications
(39 reference statements)
1
18
0
Order By: Relevance
“…A total of 14 (42%) papers addressed reasons for loss of data and issues with adherence to protocol, including technical issues (n=5, 36%) [30][31][32][33][34], participants removing or refusing to wear devices (n=6, 43%) [30,33,[35][36][37][38], insufficient data collected (n=8, 57%; <10 hours per day for 8/14 days [39]; <80% daily wear time [40]; <3 days [31]; <10 hours per day for at least 3 days [41]; <7 days [15]; <6 consecutive days [33]; incomplete recorded days [34,40]), lost devices (n=2, 14%) [15,33], organizational issues (n=2, 14%) [15,33], forgetting to wear the device (n=1, 7%) [42], and hospitalization during the data collection period (n=1, 7%) [38].…”
Section: Measuring Physical Activity In Community Dwellers With Cogni...mentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 14 (42%) papers addressed reasons for loss of data and issues with adherence to protocol, including technical issues (n=5, 36%) [30][31][32][33][34], participants removing or refusing to wear devices (n=6, 43%) [30,33,[35][36][37][38], insufficient data collected (n=8, 57%; <10 hours per day for 8/14 days [39]; <80% daily wear time [40]; <3 days [31]; <10 hours per day for at least 3 days [41]; <7 days [15]; <6 consecutive days [33]; incomplete recorded days [34,40]), lost devices (n=2, 14%) [15,33], organizational issues (n=2, 14%) [15,33], forgetting to wear the device (n=1, 7%) [42], and hospitalization during the data collection period (n=1, 7%) [38].…”
Section: Measuring Physical Activity In Community Dwellers With Cogni...mentioning
confidence: 99%
“…Of the 13 (39%) studies reporting HPA in MCI, 8 (62%) characterized volumes [32,34,40,41,[43][44][45][46][47]. The most common volume metric was steps per day (n=5, 39%), with mean/median averages ranging between 3407 and 12,256 steps [40,41,43,44,46,47]. Two (15%) studies reported time spent walking per day, with a mean range between 113 and 150 minutes [41,44].…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies explored associations between objective accelerometer-derived measures and widely used in-person assessments (e.g., TUG) and paper-based tools that assess function (e.g., ALS Functional Rating Scale-Revised), mobility (e.g., Parkinson's Disease Questionnaire (PDQ) mobility scores), or PA (e.g., Physical Activity Scale for the Elderly) [20,[26][27][28]34,36,39,43,46,59]. Furthermore, nine of the studies explored relationships between sensor-derived activity measures and disease stage, duration, or progression [20,27,28,30,34,35,39,40,45]. One study proposed that assessing physical behaviour patterns, particularly sedentary bouts, could potentially be used to discriminate between PD with mild cognitive impairment and PD with dementia [40].…”
Section: Use Of Accelerometry To Measure Pa In Nddsmentioning
confidence: 99%
“…Furthermore, nine of the studies explored relationships between sensor-derived activity measures and disease stage, duration, or progression [20,27,28,30,34,35,39,40,45]. One study proposed that assessing physical behaviour patterns, particularly sedentary bouts, could potentially be used to discriminate between PD with mild cognitive impairment and PD with dementia [40]. Kim et al reported that, in PD, the number of steps recorded by wrist-worn devices were significantly higher than those recorded by waist-worn devices (p < 0.001).…”
Section: Use Of Accelerometry To Measure Pa In Nddsmentioning
confidence: 99%